2012
DOI: 10.1136/annrheumdis-2012-201497
|View full text |Cite
|
Sign up to set email alerts
|

The burden of carotid artery plaques is higher in patients with psoriatic arthritis compared with those with psoriasis alone

Abstract: PsA patients suffer from more severe subclinical atherosclerosis compared with patients with PsC. This difference is independent of traditional cardiovascular risk factors and correlates with PsA disease duration, more severe skin disease and increased inflammatory markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
43
0
7

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 75 publications
(52 citation statements)
references
References 23 publications
2
43
0
7
Order By: Relevance
“…Our study showed that the risk for cardiac arrhythmia is higher in patients with psoriasis than in the general population, even after adjustment, suggesting the involvement of J AM ACAD DERMATOL VOLUME jj, NUMBER j other factors intrinsically linked to psoriasis and independent of the development of structural heart diseases (eg, heart failure and ischemic heart disease). Moreover, PsA, which includes inflammation of skin and joints, [20][21][22] was associated with a greater risk of arrhythmia, further indicating that inflammation may be an important link between arrhythmia and psoriasis. Among various subtypes of arrhythmia, psoriasis carried the highest risk for paroxysmal supraventricular tachycardia.…”
Section: Discussionmentioning
confidence: 95%
“…Our study showed that the risk for cardiac arrhythmia is higher in patients with psoriasis than in the general population, even after adjustment, suggesting the involvement of J AM ACAD DERMATOL VOLUME jj, NUMBER j other factors intrinsically linked to psoriasis and independent of the development of structural heart diseases (eg, heart failure and ischemic heart disease). Moreover, PsA, which includes inflammation of skin and joints, [20][21][22] was associated with a greater risk of arrhythmia, further indicating that inflammation may be an important link between arrhythmia and psoriasis. Among various subtypes of arrhythmia, psoriasis carried the highest risk for paroxysmal supraventricular tachycardia.…”
Section: Discussionmentioning
confidence: 95%
“…Some of the patients included in this study had carotid artery ultrasound and plaque area measured 18. An analysis of those who participated in both studies revealed a correlation between plaque area and HOMA-IR (data not shown).…”
Section: Discussionmentioning
confidence: 96%
“…In addition, we were unable to precisely quantify lifetime dosages of medications to examine more fully the effect of pharmacologic therapy on the development of atherosclerosis. Third, as patients with PsA suffer from more severe subclinical carotid atherosclerosis compared with patients with psoriasis (PsO),40 it would be interesting to include patients with PsO to address whether this is also true for coronary atherosclerosis. Fourth, disease activity in these patients with PsA was low to moderate.…”
Section: Discussionmentioning
confidence: 99%